2012
DOI: 10.1682/jrrd.2011.02.0015
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of screen-based symptoms for mild traumatic brain injury and mental health problems in Iraq and Afghanistan veterans: Distinct or overlapping symptoms?

Abstract: Abstract-This study used factor analytic techniques to differentiate distinct from overlapping screen-based symptoms of traumatic brain injury (TBI), posttraumatic stress disorder (PTSD), and depression in Iraq and Afghanistan veterans. These symptoms were derived from screen results of 1,549 veterans undergoing Department of Veterans Affairs postdeployment screening between April 2007 and January 2010. Veterans with positive TBI screens were approximately twice as likely to also screen positive for depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 24 publications
(27 reference statements)
0
17
0
Order By: Relevance
“…In particular, postconcussive cognitive symptoms attributed to mTBI, such as trouble with memory and attention, have long been understood to overlap with symptoms of PTSD and depression [14][15][16]. Hoge et al found that, of Operation Iraqi Freedom (OIF) servicemembers who reported mTBI with loss of consciousness for <30 min, 44 percent met criteria for PTSD and 23 percent met criteria for depression [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, postconcussive cognitive symptoms attributed to mTBI, such as trouble with memory and attention, have long been understood to overlap with symptoms of PTSD and depression [14][15][16]. Hoge et al found that, of Operation Iraqi Freedom (OIF) servicemembers who reported mTBI with loss of consciousness for <30 min, 44 percent met criteria for PTSD and 23 percent met criteria for depression [2].…”
Section: Introductionmentioning
confidence: 99%
“…While mTBI has been shown to have unique effects on health and functioning [20][21][22][23], we focus on the overlap of mTBI with PTSD and depression because these most commonly present together, and cognitive complaints are important overlapping features of all three conditions [11][12][13][14][15][16]. We hypothesize that self-reported cognitive symptoms that adversely affect daily functioning at the level of moderate to very severe are more strongly associated with individual mental health disorders and with mental health disorders in conjunction with mTBI than with mTBI alone.…”
Section: Introductionmentioning
confidence: 99%
“…The results suggest that sleep problems may be an early indicator of risk for PTSD or depression in TBI. Further, there is evidence that sleep problems can be considered a separate post-deployment health problem, distinct from PTSD, TBI, and depression (Maguen, Lau, Madden, & Seal, 2012). These and other research findings highlighted in this review, despite their methodological limitations, provide future research directions and suggest that early identification and treatment of sleep disturbance may potentially prevent the development and improve the outcome of mental health disorders, such as PTSD and depression.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of sleep as a distinct post-deployment factor (Maguen et al, 2012) highlights the need to address sleep disturbances in the clinical screening process and to develop sleep-specific treatment protocols. Moreover, sleep treatment has the potential to provide a non-stigmatizing entry into mental health services by focusing on a topic that Veterans may not consider to be ‘mental health treatment’, thereby maximizing engagement in treatment (Epstein, Babcock-Parziale, Herb, Goren, & Bushnell, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…13 Mental health issues, such as post-traumatic stress disorder (PTSD) and depression, also are strongly associated with TBI, especially in combat. 6,[14][15][16] Physical disturbances also are observed with TBI. Headache.…”
Section: Introductionmentioning
confidence: 99%